Multimodal noncontact atomic force microscopy and Kelvin probe force microscopy investigations of organolead tribromide perovskite single crystals - Almadori, Yann; Moerman, David; Martinez, Jaume Llacer; Leclère, Philippe; Grévin, Benjamin (Beilstein Journal of Nanotechnology, 2018)
In this work, methylammonium lead tribromide (MAPbBr3) single crystals are studied by noncontact atomic force microscopy (nc-AFM) and Kelvin probe force microscopy (KPFM). We demonstrate that the surface photovoltage and crystal photostriction can be simultaneously investigated by implementing a specific protocol based on the acquisition of the tip height and surface potential during illumination sequences. The obtained data confirm the existence of lattice expansion under illumination in MAPbBr3 and that negative photocarriers accumulate near the crystal surface due to band bending effects. Time-dependent changes of the surface potential occurring under illumination on the scale of a few seconds reveal the existence of slow ion-migration mechanisms. Lastly, photopotential decay at the sub-millisecond time scale related to the photocarrier lifetime is quantified by performing KPFM measurements under frequency-modulated illumination. Our multimodal approach provides a unique way to investigate the interplay between the charges and ionic species, the photocarrier-lattice coupling and the photocarrier dynamics in hybrid perovskites.
Keywords: carrier lifetime; ion migration; Kelvin probe force microscopy (KPFM); noncontact atomic force microscopy (nc-AFM); organic–inorganic hybrid perovskites; photostriction; single crystals; surface photovoltage (SPV); time-resolved surface photovoltage